Phoenician communities in the Roman world: the case of Hispania - Machuca Prieto, Francisco (My University, 2017)
This poster aims to report the conclusions of our PhD thesis, titled The Phoenician communities of the Iberian Peninsula and their integration in the Roman world: an identity perspective. The period under discussion extends from the end of the Second Punic War in 206 BCE to the Flavian era (mid-first century CE). Above all, our dissertation focuses on the cultural and ethnic dimensions of the process of integration of communities of Phoenician origin and tradition in the southern part of the Iberian Peninsula into the structures of Roman Empire. The theoretical framework which we take as our starting point rests on two pillars: - Social Constructivism. - Postcolonial Theories.
Keywords: Roma - Historia; Fenicios